Exploring the post-Covid L2 motivational disposition of English majors: An interview study at a Hungarian university - Kaw, Mai Nelly (Working Papers in Language Pedagogy, 2024)
Covid-19 rapidly shifted learning and teaching to online platforms, significantly impacting students’ learning worldwide (Huang & Wang, 2022). The transition from the pandemic to the post-pandemic period has changed views on learning activities, affecting students’ motivation to learn (Firmansyah et al., 2023). During the pandemic, Hungarian university students transitioned to online education. However, research on post-covid motivational disposition of Hungarian university students, especially English majors studying English as a foreign language (EFL), remains scarce. Therefore, this study explores post-covid English majors’ L2 motivational disposition in Hungarian tertiary education because research shows that motivation is crucial for long-term success in language learning (Dörnyei & Ryan, 2015; Lamb, 2017). To gain rich, in-depth data on participants’ opinions and personal experiences, qualitative data were collected via semi-structured interviews with eleven English BA students in Hungary. Thematic analysis revealed various motives, including ideal and ought-to L2 selves, the L2 learning experiences, the influence of significant others, the teacher’s role, instrumentality, intrinsic motivation, and international posture. Findings also show greater motivation in traditional in-person classes over online classes. The implications of this study yield valuable insights for EFL teachers into what motivates their students to learn EFL and their pivotal role in the students’ language learning. Keywords: EFL, L2 motivational disposition, post-covid English majors, interview study, Hungarian tertiary education